Technical Challenges Involved in Implementation of VOC Reactivity-Based Control of Ozone - Luecken, D. J; Mebust, M. R (Environmental science & technology, 2008)
Controlling VOC emissions on the basis of their individual contribution to ozone formation has been subject to extensive discussion and research in past years, and the concept has gained some acceptance in the air pollution community for certain product categories and industrial operations. Despite its potential to decrease ozone formation, there are some technical challenges that still remain before we can confidently apply the concept of reactivity in the most beneficial manner to reduce ozone concentrations. The goal of this paper is to (1) assess how existing science in this area supports the use of reactivity, particularly, the maximum incremental reactivity, for VOC control under a national policy application and (2) identify where uncertainties exist that could affect such a policy. Box model and air quality model results are used to show that there are ways to describe a chemical’s reactivity that are relatively robust across large geographic areas. Modeling results also indicate that the choice of metric is important in determining the potential benefits and detriments of a reactivity-based emission control policy.